Cleaning up the "Fetid Swamp": Examining how journalists construct policies and practices for moderating comments. Issue 1 (2nd January 2018) - Wolfgang, J. David
Abstract : Online commenting has become a popular form of audience–journalist interaction. However, journalists have become frustrated with commenters who use forums to attack and make assertions. As journalists look for ways to reign in commenters, it becomes important to consider how journalists make decisions about moderation policies and practices. This study used gatekeeping theory to consider how one organization approached moderation and related issues of content management. The researcher conducted a one-month ethnography of a large news organization and their online forums and discovered that journalists set high expectations of commenters, but willingly accept low-quality content. Journalists appear to struggle with how to institute policies that promote high-quality discourse without engaging in intense battles with the audience and having to devote more resources to moderation. Journalists focus on establishing balance between allowing the audience to have a conversation without allowing that conversation to disrupt the traditional practices of journalism.